Net Promoter Score Model for Evaluating Paediatric Medicine Acceptability: Validation and Feasibility Study - Okhee Yoo; Demi Stanford; Britta S. von Ungern-Sternberg; Lee Yong Lim (Pharmaceutics, 2024)
Background/Objectives: Medicine acceptability is crucial for paediatric drug development, yet its assessment remains challenging due to the multifaceted nature of sensory attributes like taste, smell, and mouthfeel. Traditional methods of acceptability evaluation often involve complex questionnaires and lack standardisation, leading to difficulties in a comparative analysis across studies. This study aimed to develop a simplified, standardised approach for assessing medicine acceptability introducing the Net Promoter Score (NPS) framework to derive a Medicine Acceptability Score (MAS). Methods: A retrospective analysis was conducted using taste assessment data from nine paediatric formulations across four studies. The MAS was calculated by identifying an optimal range for categorising participant responses, which encapsulated diverse sensory attributes into a single metric. Validation was performed across various age groups and different formulations to test the reliability and discriminatory power of MAS. Results: The MAS effectively discriminated between acceptable and unacceptable formulations, providing a practical tool for formulation development. Conclusions: The MAS offers a novel, standardised metric for evaluating paediatric medicine acceptability, addressing key limitations of traditional methods. Future studies are recommended to refine the MAS model through the establishment of benchmark scores for chronic and acute medications, thereby standardising acceptability assessment of medicines across the pharmaceutical industry.